(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2024)
This article is based on the master’s thesis "Profession: Journalism Teacher - The knowledge needed for teaching practice". Understanding who are the journalists who became teachers, what path they followed and how they prepared themselves for the pedagogical mission was what motivated the research, which used the teaching knowledge described by Tardif (2012) and Freire (2009). The methodology was life stories, with interviews. Four professors from two journalism courses told their life and professional trajectory. The answers, after being analyzed, were divided into categories created by the researchers based on those already existing and described by the reference authors. As conclusions we corroborate that the knowledge of teachers originates in practice and is acquired over time in the experience and exchange with students, but this experiential knowledge is still the only knowledge that governs teachers in higher education because there is no pedagogical training for university teaching in most Brazilian undergraduate courses. While a pedagogy of journalism is being built, the research pointed out that the knowledge needed to be a journalism teacher is: to be a graduate journalist, to want to be a teacher, to have gone through graduate studies, to have a minimum knowledge of the journalism job market, to be always up to date, to understand that teaching is learned by being a teacher, to be capable of constant dialog with students, to visualize that the professional practice of journalism - by itself - does not make one a teacher, to understand that teaching is a human specificity, to participate in continued training, to understand the responsibility for the training of new journalists.